1990
DOI: 10.1246/bcsj.63.1738
|View full text |Cite
|
Sign up to set email alerts
|

A Grignard-Type Addition of Allyl Unit to Aldehydes by Using Bismuth and Bismuth Salt

Abstract: In the presence of metallic bismuth, bismuth(III) chloride–metallic zinc, or bismuth(III) chloride–metallic iron, allylic halides have been found to react with aldehydes under mild conditions to give the corresponding homoallylic alcohols in high yields with high chemo-, regio-, and stereoselectivity. Allylic halides have been also found to react with aldehydes at room temperature in tetrahydrofuran–water by using bismuth(III) chloride–metallic aluminium to afford the expected homoallylic alcohols in high yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…We began with BiCl 3 -mediated allylation39 of ethyl glyoxalate to furnish homoallylic alcohol 92 as an inconsequential mixture (ca. 1:1) of isomers (Scheme 33).…”
Section: Resultsmentioning
confidence: 99%
“…We began with BiCl 3 -mediated allylation39 of ethyl glyoxalate to furnish homoallylic alcohol 92 as an inconsequential mixture (ca. 1:1) of isomers (Scheme 33).…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, Xu et al found nano-Bi to be more effective than regular Bi-powder, although this method had an intrinsic difficulty of preparing Bi-nanoparticles via reduction of Bi(III) salts [35]. These apart, combinations of Bi(III) salts with reducing metals, e.g., Mg-BiCl 3 [36], Fe-BiCl 3 or Zn-BiCl 3 [30], and Al-BiCl 3 [37] have been used. Aqueous NH 4 Cl was also employed as an additive in the Al/BiCl 3 mediated allylation of carbonyls in aqueous THF [38].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a considerable interest in developing organometallic reactions in water, of which allylation of aldehydes and ketones to give homoallylic alcohols has been regarded widely. 1 This reaction has been achieved by using metals such as Mn/Cu, 2 Sn, 3 Zn, 4 Bi, 5 In, 6 Mg, 7 Ga, 8 or organometallic compounds such as diallylmercury, allylmercurybromide, 9 allyltributylstannanes 10 and tetraallylgermane. 11 Previously indium was reported to mediate Barbier-Grignard and pinacol coupling type reactions in water, 6 subsequently, gallium also was used to carry out the Barbier-Grignard and pinacol coupling type reactions in water.…”
Section: Introductionmentioning
confidence: 99%